Diagenetic facies of the Fengcheng Formation tight reservoir in the alkaline lake sedimentary environment, the southern margin of Mahu Sag, Junggar Basin, China - Zongbin Zhang; Jun Qin; Zhongchen Ba; Wenbiao Huang; Mengyun Han; Yuhui Gao; Dong Wu (Journal of Natural Gas Geoscience)
With the aim of exploring the diagenetic characteristics, influence mechanisms, and distribution of dominant diagenetic facies in the Fengcheng Formation, at the southern margin of Mahu Sag in the Junggar Basin, this paper quantitatively characterized the reservoir transformation intensity of compaction, cementation, and dissolution on the basis of the analysis of petrological characteristics, pore types, diagenesis, and diagenetic environment evolution, and established a diagenetic facies division scheme. Based on single-well core interval evaluations, the diagenetic facies distribution was described, and the mechanisms influencing their distribution were explained. The results show that the reservoir space in the Fengcheng Formation is characterized by a dual medium of “matrix-pores dominated and micro-fractures supplemented”, with intra- and intergranular dissolved pores being predominant types in matrix pores. The Fengcheng Formation underwent an evolution through an alkaline sedimentary environment and an alkali-acid-alkaline diagenetic sequence. During the alkaline sedimentary and early alkaline diagenetic stages, significant intergranular pore loss occurred due to cementation, while volcanic material hydrolysis and plagioclase albitization facilitated the formation of solution pores. The reaming in the acidic diagenetic environment in the middle stage caused additional dissolution pore become the main reservoir space, and mitigating the densification to some extent. In the late alkaline diagenetic environment, the concentration of alkaline mineral ions increased, leading to precipitation in the remaining intergranular pores, solution pores, and other reservoir spaces, and the reservoir densification degree is further improved. In the study area, the cementation and dissolution of fan delta plain and front junction were weak, resulting in more compact phases developed, with an average porosity of about 4.9%. Moving from the inner front of the fan delta to the junction of the outer front, dissolution became more dominant than cementation, leading to development of cementation-dissolution phases, with an average porosity of about 6.6%. The dissolution phases near the central and southern faults prevailed, with an average porosity of 9%. The outer front of the fan delta is mostly associated with solution-cementation facies, resulting in an average porosity of the reservoir of about 3.1%. In general, alkaline diagenesis in the alkaline lake sedimentary setting has a dual effect on reservoir reconstruction. The cementation-dissolution and dissolution phases, under the control of acid/alkaline dissolution process, are favorable sites for tight oil accumulation in this area, and are also the key factors for the high productivity in this area.